2007
DOI: 10.1096/fj.07-8888com
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of human ferrochelatase causes abundant protoporphyrin‐IX accumulation in colon cancer

Abstract: Hemes and heme proteins are vital components of essentially every cell of virtually every eukaryote organism. Previously, we demonstrated accumulation of the heme precursor protoporphyrin-IX (PpIX) in gastrointestinal tumor tissues. To elucidate the mechanisms of PpIX accumulation by quantitative reverse transcriptase-polymerase chain reaction (RT-PCR), we studied expression of the relevant enzymes of the heme synthetic pathway. Here, we describe a significant down-regulation of ferrochelatase (FECH) mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 26 publications
6
96
0
Order By: Relevance
“…This team and others suggested that PpIX formation in human cancers, especially as a response to ALA medication, might be related to lowered FECH enzyme activity. Moreover, Kemmner and colleagues (16) were able to demonstrate a significant downregulation of FECH mRNA expression in gastric, colonic, and rectal carcinomas. These data were used as a rationale for the use of photodynamic therapy (PDT) supplemented with exogenously added ALA in particular on urothelial carcinoma (17).…”
Section: Discussionmentioning
confidence: 94%
“…This team and others suggested that PpIX formation in human cancers, especially as a response to ALA medication, might be related to lowered FECH enzyme activity. Moreover, Kemmner and colleagues (16) were able to demonstrate a significant downregulation of FECH mRNA expression in gastric, colonic, and rectal carcinomas. These data were used as a rationale for the use of photodynamic therapy (PDT) supplemented with exogenously added ALA in particular on urothelial carcinoma (17).…”
Section: Discussionmentioning
confidence: 94%
“…Other already mentioned approaches include improving ALA-induced PpIXmediated PDT selectively by using the already mentioned siRNA to down-regulate ferrochelatase. 41 Photofrin and other photosensitizers (mTHPC), including Talapor¯n sodium, and BPD have a somewhat di®erent subcellular distribution and can be found in the plasma membrane of cells when the BBB is compromised or in the vascular endothelial cells within the intact blood vessels and as such the cellular damage dynamics and the dose response are di®erent. Dereski et al 80 determined that Photofrin and similar photosensitizers do not require subcellular uptake to elicit a PDT e®ect on normal brain tissues or tumor.…”
Section: Cellular Responses To Pdt and Options For Selectivity Modulamentioning
confidence: 99%
“…2). 40 Kemmner and colleagues 41 showed that down regulation of the ferrochelatase gene expression is further augmented by siRNA in glioblastoma culture leading to a higher accumulation of PpIX. However, the inherent sensitivity and responsivity of the involved cells and tissues, such as GBM cells versus normal astrocytes, neurons and glial cells, dictate the attainable selectively of the PDT e®ect, as will be explained below.…”
Section: Introductionmentioning
confidence: 99%
“…[137] These authors postulated that endogenous PpIX accumulates as a result of aberrant metabolic changes in the CRC cells; Kemmner et al [138] subsequently provided supporting evidence for this hypothesis by showing that there is a significant down-regulation of ferrochelatase (FECH) mRNA expression in gastric, colon, and rectal carcinomas, leading to accumulation of PpIX. In an effort to utilise this information Moesta et al [137] found that metastatically involved lymph nodes could be identified compared to all other palpable nodes; in the context of previously untreated patients (n=24), this observation had a sensitivity of 62% and a specificity of 78% (p < 0.0001).…”
Section: Molecular Imagingmentioning
confidence: 99%